Strategi Guru Dalam Meningkatkan Kedisiplinan Belajar Siswa Di SDN 5 Kabila Kabupaten Bone Bolango - Yeti Suhesti Maudi; Thamrin A. Kum; Yusraningsih H. Pongoliu (Transbahasa, 2026)
This study aims to describe and analyze teachers’ strategies in improving students’ learning discipline at SDN 5 Kabila, Bone Bolango Regency. This research employed a qualitative approach with a descriptive design. The research subjects consisted of three classroom teachers and a principal selected through purposive sampling. Data were collected through observation, interviews, and documentation, while data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that teachers implement four main strategies to improve students’ learning discipline, namely habituation, advice, reprimand, and educational sanctions. Habituation becomes the most dominant strategy because it is consistently integrated into daily learning activities. Advice and reprimand function to strengthen students’ awareness regarding the importance of discipline, while educational sanctions serve as corrective consequences to prevent repeated violations. The effectiveness of these strategies is influenced by internal factors such as students’ learning motivation and external factors including family and social environment. Therefore, consistent, integrated, and contextual strategies are needed in accordance with students’ characteristics. This study contributes to strengthening the literature regarding teacher strategies in fostering learning discipline in primary education through a qualitative contextual perspective.